Tradisi Kenduri Laut Masyarakat Pantai Barus: Penetrasi Nilai-Nilai Sufistik-Islam dan Modernitas dalam Perspektif Hukum Islam - Ahmatnijar; Risalan Basri Harahap; Puji Kurniawan (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This article aims to examine the tradition of sea feasts on Barus Beach, because this tradition is a cultural heritage that is firmly rooted in the lives of coastal communities as a form of expression of gratitude to Allah SWT for marine products and prayers for the safety of fishermen. Along with the development of the times, this tradition has experienced dynamics due to the penetration of Sufistic-Islamic values mixed with local culture and the influence of modernity that changes people's perspective on religious practices. This study uses a qualitative method with a descriptive-analytical approach, with data collected through literature studies, participatory observations, and in-depth interviews with religious leaders, traditional actors, and local communities. The results of the study show that the Sea Kenduri has a sufistic element that is reflected in the practice of dhikr, prayer, and tahlil, which is rooted in the teachings of the tariqat that developed in Barus. From the perspective of Islamic law, this tradition can be categorized as 'urf sahih as long as it does not contain elements that are contrary to the principle of monotheism. However, modernity brings challenges in the form of shifting values among the younger generation, which increasingly questions the relevance of this ritual in the context of contemporary Islam. Therefore, it is necessary to reconstruct this tradition so that it remains in harmony with sharia values without losing the essence of culture and spirituality that has long been inherent in the lives of the people of Barus Beach.